Nonprofit marketing: marketing management for charitable and nongovernmental organizations - Wymer, Walter; Knowles, Patricia; Gomes, Roger (London, 2006)
"Perhaps now more than ever, effective marketing is crucial in successfully managing a nongovernmental organization. A nonprofit organization that is effectively using marketing strategies is better positioned to present a consistent and memorable image of its cause to policy makers, funding organizations, individual contributors, and society at large. A successfully marketed charity is able to distinguish itself from other organizations in the continually growing nonprofit sector. It is able to share its cause and importance to the public, demonstrating its value, while communicating its unique purpose and mission. Nonprofit Marketing explains marketing management concepts and applications in nonprofit, charitable and nongovernmental organizations in an easy-to-follow style. Marketing concepts are clearly presented, then supported with real-world examples.It offers examples from around the world and is applicable to all international nongovernmental and nonprofit organizations."